ANALISIS PENGARUH INDUSTRI PARIWISATA TERHADAP PENYERAPAN TENAGA KERJA DI INDONESIA - Annisa Nur Pita; Saiqa Ilham Akbar (Politeknik Negeri Batam, 2019)
In 2017, the growth of the tourism sector in Indonesia ranked the ninth highest in the world (WTTC, 2018). Growth in the tourism sector also has an impact on employment in this sector. This study aims to estimate the effect of the development of the tourism industry on employment in the tourism sector and how much influence. The data used is secondary data from BPS. The form of data is panel data consisting of time series data and cross sections. The time series data is in 2010-2016 while the cross section data consists of 34 provinces in Indonesia. The analytical tool used is regression with panel data. The results of the fixed effect model panel regression can be seen that the probability value of each independent variable is less than the critical value of 5% (0.05). Then it can be concluded that the variable Number of Star Hotels, Number of Non-Star Hotels, Number of Domestic Tourists and Number of Foreign Tourists has a significant and positive effect on the Labor variable in Indonesia. The more the number of star hotels, the number of non-star hotels, the number of domestic tourists and the number of foreign tourists, the higher the absorption of the workforce in the tourism sector.